Interpretation of the Constitution Regarding the Presidential Term - Jaya, Hendra; Kristanto, Budi (Universitas Islam Lamongan, 2024)
Abstract The limitation of the presidential term has become one of the mandates of the 1945 Constitution of the Republic of Indonesia (UUD 1945), serving as the foundation for various laws in Indonesia. The restriction on the presidential term, allowing a president to be elected for only two consecutive or non-consecutive terms, imposes additional demands on the president to build Indonesia in line with prevailing ethical standards. However, issues arose in the year 2021 when there was discourse regarding the extension of the presidential term, leading to various parties presenting arguments on the matter. Therefore, researchers intend to conduct a study to interpret the UUD 1945 regarding the limitation of the presidential term using a normative juridical method. The researchers found that the UUD 1945 concerning the limitation of the presidential term can be interpreted as a means to avoid absolute power, enhance transparency, ensure the balance of the trias politica, increase participation and dialogue with the public, and promote the president's compliance with prevailing ethical standards.